The Exposure of Honey Bees to Pesticide Residues in the Hive Environment with Regard to Winter Colony Losses - Pohorecka, Krystyna; Szczęsna, Teresa; Witek, Monika; Miszczak, Artur; Sikorski, Piotr (Journal of Apicultural Science, 2017)
The present studies are the second part of the research project dedicated to finding the causes for increased winter mortality of honey bee colonies. The aim of this task was to investigate incidents of overwintered colonies′ death with regard to the potential interrelation to the exposure to pesticides. The samples of winter stores of bee bread and sugar food (honey or syrup processed by bees), beeswax and bees collected from apiaries with low and high rates of winter colony mortality were searched for acaricides used to control V. destructor and plant protection pesticides. The presence of acaricides used in apiculture has been detected in the 51% beeswax samples. The most abundant acaricide was tau-fluvalinate. The stores of bee bread and sugar food had a similar frequency of plant protection pesticide occurrence, ranging between 50-60%, but the number of active substances and their concentrations were substantially lower in sugar food samples. The most prevalent pesticides in pollen were fungicides (carbendazim and boscalid) and insecticides (acetamiprid and thiacloprid). Only a few pesticides were found in the several dead honey bees. The level of pesticide contamination (frequency, concentration, toxicity) of hive products and bees originating from apiaries with both a high and low winter colony survival rates, was similar, which created a similar extent of risk. Although the multiple varroacides and pesticides were present in the hive environment we not found unequivocal links between their residues and high winter colony mortality.